(untitled) (Biological Sciences - PJSIR, 1999)
Caffeine, an important member of methylxanthines, induced aprolonged nocturnal rise in pineal melatonin content and an increase in its rate-limiting enzyme serotonin N-acetyltransferase (NAT) activity. The highest levels were reached five hours after subcutaneous caffeine injection to male rats in the dark phase, where the NAT activity increased from 920±70 pM pineallh’ in the control group to 1190±120 pM pineal+b’ (p<O.OOI)in the treated group. The pineal melatonin content, as well, was elevated from 520±40 pg pineal’! in the control group to 1120±80 pg pineal’! (p<O.OOI) in caffeine treated group. These changes could be attributed to the depressive effect of caffeine on the activity of phosphodiesterase (PDE), the enzyme responsible for the hydrolysis of the intracellular second messenger cyclic adenosine monophosphate (cAMP).